Successes and problems of "re-education": to the 70th anniversary of completion of denazification of Germany - Tetіana Kuprii (Cхід, 2018)
In the article the various social aspects of policy of denazification ofGermanyare probed in 1945-1948, which were stopped up in basis of spiritual and cultural revival of the post-war state. Basic measures and actions of organs of occupation power of allies are examined on "re-education" of Germans after the crash of national socialism and blowing off political and ideological bases of German society of in general.